PENGARUH IKLIM ORGANISASI DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT IDANOTAE KABUPATEN NIAS SELATAN - Anuarman Lase (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The problem of this research is that the level of individual contribution or performance that is expressed in completing the tasks for which they are responsible is still low. This studuy aims to determine the efeect of organizational climate and career development on employee performance at the idanotae sub-district office, south Nias district. This type of research is quantitative. The population in this study were all employees opf the idanotae sub-district office, South Nias district, with total sample of 31 people. Data analysis method used in research is multiple regression. The results of this study indicate dhat the influence of orgsnizatinal climate and career development on employee performance at the idanotae sub-discrict. The suggestions put forward by researchers are 1) the head of the idanotae sub-district, needs to have the ability to manage employee performance properly, and 2) employees of the idanotae sub-discrict office, south Nias discrict, sould improve competence in each of their respective fields in order to get opportunities to be placed in a higher position.